VALIDATION OF LEARNING EVALUATION QUESTIONNAIRE IN FACULTY OF MEDICINE PATTIMURA UNIVERSITY - Nerissa Alviana Sutantie; Farah Christiana Noya; Rif'ah Zafarani Soumena (Molucca Medica, 2020)
Abstract: Efforts to guarantee the quality of medical doctor graduates are major concern in the implementation of problem-based learning in medical education today. Therefore, continuous evaluation in the medical education system is necessary. However, to obtain constructive evaluation results, the instrument that is used must be valid and reliable. This study aimed to validate the learning evaluation questionnaire used at the Faculty of Medicine Pattimura University, so the valid and reliable instrument can be produced for further evaluation. This study used correlative analytic method; with study subject are 102 students that were selected randomly through stratified random sampling technique and had been adjusted to restriction criteria. Pearson bivariate correlation test was performed to obtain the validity coefficient and the reliability coefficient by Alpha method. The results of the initial analysis and the second analysis after modification show that some items have low validity (0.311 and 0.256) and even invalid (- 0.03; < r table 0.1946). However, after item reconstruction, the average validity coefficient raise to >0.5 (moderate category) and >0.9 (very high category) with the overall questionnaire reliability coefficient is >0.9 in two tests (test-retest). Thus, it can be concluded that the learning evaluation questionnaire used at the Faculty of Medicine Pattimura University is valid and reliable.